COMPARISON OF THE EFFICIENCY OF NON-PENETRATING DEEP SCLERECTOMY AS A STANDALONE SURGERY AND MODIFIED NON-PENETRATING DEEP SCLERECTOMY IN COMBINATION WITH AB INTERNO ENDOTRABECULECTOMY - Olha Levytska; Ihor Novytskyi (Acta Medica Leopoliensia)
Aim. To compare the hypotensive effect of non-penetrating deep sclerectomy (NPDS) as a standalone surgery and non-penetrating deep sclerectomy in combination with dosed endotrabeculectomy in patients with primary open-angle glaucoma.